Intergenerational redistribution with asymmetric information: The case of non-observable savings - Jens Oliver Lorz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
This paper analyzes intergenerational redistribution in a 2-period overlapping- generations model that allows for heterogeneous labor productivities within the working generation. In each period, the government decides about redistributive transfers to maximize the aggregate utility of the members of both generations. There is asymmetric information between the government and the private sector: The government can only observe labor incomes but not individual labor supply or individual productivities. In addition, individual savings and capital incomes are not observable for the government. It is shown that the political economy equilibrium is not Pareto-efficient. Redistribution results in equal consumption levels of individuals with different labor productivities. This destroys incentives for individuals with a high labor productivity to earn a higher labor income than individuals with a low labor productivity.
Keywords: E62; D78; D82; 330; Overlapping generations; redistribution; political economy; asymmetric information; Einkommensumverteilung; Generationenbeziehungen; Overlapping Generations; Public Choice; Sparen; Intertemporale Allokation; Pareto-Optimum; Asymmetrische Information; Ökonomischer Anreiz; Theorie